Mathematical Model of VPN in a Special Purpose Telecommunication Network - S. S. Vrublevsky; E. V. Mashkin; A. A. Bysov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The purpose of the article is to develop a mathematical model of VPN in communication networks of special purpose, which allows to determine the margin of throughput, for scheduled VPN-tunnels. In contrast to the well-known approaches to estimating the bandwidth margin (hose model of VPN), the developed model takes into account the class of transmitted traffic. The developed model is adequate with an accuracy of 0.95. The materials presented in the article are original and can be used when planning VPN-tunnels in a special purpose telecommunication network.